Peran Mahasiswa Ppl Dalam Meningkatkan Motivasi Belajar Siswa Di Mas As-Tsaqhofah - Akbar Hasan Habibi; Nur Afni Lubis; Safri Efendi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The enthusiasm for PPL and Practicum for STAIN MADIN students was very enthusiastic when they did their internship at MAS As-Tsaqhofah Bukit Malintang. This PPL was attended by students from across study programs such as PBA, MPI, and PAI. In this PPL, STAIN MADINA students carry out various activity programs to increase students' interest in learning by using learning media, carrying out various activities, and involving students in various activities and events held at STAIN MADINA. Also in the field of Educational Management, carrying out office layout and learning to improve students' interests. PPL students have a positive influence on PAI learning motivation, which can be seen from the responses of students who feel happy learning in the presence of PPL students. The efforts made by PPL students to increase the learning motivation of As-Tsaqhofah students are carried out by creating good communication with students, implementing appropriate learning strategies.